Pengaruh Pendapatan Bagi Hasil Musyarakah, Bagi Hasil Mudharabah, dan Margin Murabahah terhadap Laba Bersih PT. Bank Muamalat Indonesia, Tbk. - Maulana, Govi; Sari, Lili Puspita (ITB AAS INDONESIA Surakarta, 2023)
One parameter to measure a bank’s success is net profit. The more the bank's revenue grows, the more it shows a strong performance. This research aims to determine the effect of revenue sharing from musyarakah, mudharabah, and murabahah margin income on the net profit of PT. Bank Muamalat Indonesia, Tbk with a time span of 2014 to 2021. The approach used in this research is a quantitative approach based on secondary data with the sample used in the report of PT. Bank Muamalat Indonesia, Tbk in 2014 to 2021. The data analysis method used is Multiple Linear Regression. The results showed that musyarakah profit-sharing income did not have a positive effect, mudharabah profit-sharing income had a positive effect, while murabahah margin income had a negative effect on net income. For the Islamic banking industry, this research can be used to determine the factors that can affect net profit and can measure the performance of Islamic banks and other stakeholders.